2008
DOI: 10.1016/j.conengprac.2007.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Emulator-based control for actuator-based hardware-in-the-loop testing

Abstract: Hardware-in-the-loop (HWiL) is a form of component testing where hardware components a linked with software models. In order to test mechanical components an additional transfer system is required to link the software and hardware subsystems. The transfer system typically comprises of sensors and actuators and the dynamic effects of these components need to be eliminated to give accurate results. In this paper an emulator-based control strategy is presented for actuator based HWiL. Emulator-based control can s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 43 publications
(45 reference statements)
2
25
0
1
Order By: Relevance
“…It was also found that in the forward‐control cases, when c 1 was reduced further, such that eig( A N11 ) = − c 1 / m 1 was very close to the imaginary axis, N2‐SSLSC tended to easily cause instability, whereas N1‐SSLSC remained stable. The unstable results corresponded to the finding in , which specifically stated that lower damping within Σ N1 had significant influence on the DSS stability. However, this study has provided a more general conclusion (or index) to determine the DSS performance: small damping of c 1 , large mass of m 1 , slow G TS or, in general, slow subeig, degrades the DSS stability and performance.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It was also found that in the forward‐control cases, when c 1 was reduced further, such that eig( A N11 ) = − c 1 / m 1 was very close to the imaginary axis, N2‐SSLSC tended to easily cause instability, whereas N1‐SSLSC remained stable. The unstable results corresponded to the finding in , which specifically stated that lower damping within Σ N1 had significant influence on the DSS stability. However, this study has provided a more general conclusion (or index) to determine the DSS performance: small damping of c 1 , large mass of m 1 , slow G TS or, in general, slow subeig, degrades the DSS stability and performance.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, {B Ni1 , B Nd1 } in (25) may not be null. The higher dimensions of {A N12 , B Ni1 , B Nd1 } and x N2 can complicate the synthesis of typical NB controllers of (9)- (12).…”
Section: The Numerical-substructure-based Substructured Framework Anmentioning
confidence: 99%
“…[31,32]). It is noted that in the DSS literature, Σ N1 , including low damping and large mass, tends to cause unstable tests [14,16,33]. This phenomenon is rationalized herein, by considering the combined numerical and dynamic properties of Σ N1 .…”
Section: Further Discussion On Adaptive Forward Prediction Control Anmentioning
confidence: 99%
“…The hardware-in-the-loop method to study the ABS can avoid some defects of the pure simulation, e.g., low precision, lack of intuition and high risk. This joint simulation combines software and real vehicles to greatly improve the experiment authenticity [4,5].…”
Section: Introductionmentioning
confidence: 99%